Pengaruh Performa Mesin Diesel Berbahan Bakar Crude Palm Oil (CPO) dan B35 Terhadap Variasi Pembebanan - SAPUTRO, WILIANDI (Creative Research in Engineering (CERIE), 2025)
One use of alternative fuel that has the potential to be developed currently is crude palm oil (CPO). However, the use of CPO must go through a series of direct tests before it is widely applied. So the aim of this research is to carry out tests related to the use of CPO fuel and determine the effects in terms of engine performance and exhaust emissions. The fuel used in this research is CPO and B35 as existing fuel. The method used is an experimental method, through direct observation and measurement of phenomena when CPO fuel is tested for performance and exhaust emissions. The research used a diesel engine coupled to a generator and loaded with halogen lamps. The loading varies, namely 0.5; 1; 1.5; 2; 2.5; 3; 3.5; 4; up to 4.5 kW. Based on research results, the use of CPO fuel in general will produce higher power, torque and SFC, namely 2.55% each; 2.55%; and 17%. However, when comparing the thermal efficiency, hydrocarbon (HC) emissions and smoke opacity of CPO fuel, it produces a lower value of 10.54%; 15.4%; and 72% compared to B35 fuel engines. This is generally influenced by CPO fuel which has a lower calorific value, viscosity value and higher density than B35.